Análise dos fragmentos de vegetação da bacia hidrográfica do Alto Jacuí para ampliação do corredor ecológico da Quarta Colônia/RS - Ziani, Patrícia (2017)
Before the importance that vegetation fragments hold for the provision of environmental services, being for biodiversity conservation or being in qualitative and quantitative improvement of hydric resources, the main objective of the present research is to analyze the fragments of Alto Jacuí Hydrographic Basin vegetation, seeking the enlargement of Ecological Corridor of Quarta Colônia. Thus, it has as specific objectives: identify, in priorities areas of RS Biodiversity project, the area of Quarta Colônia Ecological Corridor in Alto Jacuí Hydrographic Basin; delimit and map the fragments of vegetation present in Alto Jacuí Hydrographic Basin discussing the relevance of these ones both to the maintenance of biodiversity and also to the hydric processing; perform overlapping of data obtained in vegetation fragments of Alto Jacuí Hydrographic Basin with the data that indicate the limits of the Ecological Corridor of Quarta Colonia; analyze and indicate, through the principles of landscape Ecology and geo-ecology, and the possibility of expanding Ecological Corridor of Quarta Colônia through the incorporation of new fragments of vegetation from Atlantic Forest Biome present in Alto Jacuí Hydrographic Basin. To reach the proposed goals, steps were structured: definition of the theoretical investigation initial mark, primary and secondary data survey; data organization and cartographic material processing; information analysis, syntheses and integration. Among the obtained results it stands out the identification of fourteen areas to incorporate and expand the Ecological Corridor of Quarta Colônia (core zone). Those fourteen areas are parallel to the Ecological Corridor of Quarta Colônia and they give continuity to fragments of vegetation from Atlantic Forest Biome, which were already defined, by RBMA, as core zone of RBMA. About the identification of these areas, it stands out that this was only possible because the increment of the analysis scale. It is believed that the incorporation of these 14 areas in core zone of Ecological Corridor, as well as the regularization and consolidation of their APPs and incorporation of RLs associated to the same, is from the most importance and strategy for maintenance of these areas, because it expands the area, focusing in conservation of biodiversity and natural resources, guaranteeing and empowering in that way the conservation of those areas and the provision of environmental services, since the core zone is more restrictive. Thus, with this study we hope to help in discussions and process of planning that permeate the effective conservation and maintenance of the remnants from Atlantic Forest, being in Alto Jacuí Hydrographic Basin, or being in municipal scope of the municipalities that belong to it. Besides, it is expected that the results of that research instigate future labour and also conservation policies for the studied area.